Persepsi Mahasiswa Universitas Negeri Padang Terhadap Kredibilitas Informasi pada Konten YouTube Ferry Irwandi - Hilda Nurhidayati; Desriyeni Desriyeni (Lembaga Teewan Journal Solutions, 2026)
The digital transformation in the information environment has driven changes in information-seeking behavior among students, with YouTube becoming a primary source of educational content. However, the ease of access to digital information raises issues related to information credibility, necessitating critical evaluation skills for the information consumed. This study aims to describe Padang State University students' perceptions of the credibility of information in Ferry Irwandi's YouTube content. This study employed a descriptive quantitative method with a sample size of 100 respondents, determined using the Slovin formula from a population of 45,955 students and selected through purposive sampling. Data collection was conducted through a four-point Likert-scale questionnaire structured based on Information Credibility Theory, encompassing three dimensions: source credibility, content quality, and presentation. Data analysis was conducted using descriptive statistics in the form of frequency distributions and mean values ​​using SPSS. The results showed that students' perceptions of information credibility were in the high category with an overall mean value of 3.37. The source credibility dimension was in the high category with a score of 3.38, the information content quality dimension was 3.33, and the information presentation method dimension was in the high category with the highest score of 3.41. These findings indicate that students tend to assess the credibility of information based on clarity of delivery, argument structure, and visual support, compared to in-depth evaluation of the information source. Overall, Ferry Irwandi's YouTube content was perceived as credible by Padang State University students. However, improvements are still needed in the ability to critically evaluate information sources, as some students still use a heuristic approach in assessing information.